Woman in life and writings Sadegh Hedayat - Qasim, khayria Damak (Al-Adab Journal, 2020)
The personal life of Sadegh Hedayat was a special life, only a few people knew about this side of the life. It was said that when he reached Paris just a few months before he committed suicide he was already desperate, miserable and extremely hopeless. He showed no signs of interest in life. In most of his works, he expresses strange and sad sides in the relationships between man and woman; in which he had no influence over. His female casts where always imprison by their sexual desires, this is not only the case in his novel (The Woman That Lost Her Husband) but was also obvious in his other works, it is as if the character in his novels represent himself, because he was not very successful in his relationships with women. in his world he expresses that (he wishes for women to come to him) but because of his shyness and pride he did not allow himself to approach them and be rejected.